2018
DOI: 10.1051/e3sconf/20185400026
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a regional coastal zone aquifer using an interdisciplinary approach – an example from Weser-Elbe region, Lower Saxony, Germany

Abstract: In this study, interdisciplinary approaches are considered to characterize the coastal zone aquifer of the Elbe-Weser region in the North of Lower Saxony, Germany. Geological, hydrogeological, geochemical and geophysical information have been considered to analyze the current status of the aquifers. All the information collectively states that the salinity distribution in the subsurface is heterogeneous both horizontally and vertically. Early age flooding also contributed to this heterogeneity. No general clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(6 reference statements)
0
5
0
1
Order By: Relevance
“…The high electrical conductivity of groundwater in the study area (> 2000 µS/cm) is mostly dominated by chloride and sodium ions, although the piper diagram presented by Rahman et al (2018) shows that Ca(HCO3)2 and Mg(HCO3)2 are also present in the groundwater. To avoid uncertainties involved in bicarbonate measurement and to consider that the electrical conductivity is not linearly related to the Cl concentration (De Louw et al 2011), we separated the entire data set into three classes.…”
Section: Relation Between Ec W and CLmentioning
confidence: 84%
See 1 more Smart Citation
“…The high electrical conductivity of groundwater in the study area (> 2000 µS/cm) is mostly dominated by chloride and sodium ions, although the piper diagram presented by Rahman et al (2018) shows that Ca(HCO3)2 and Mg(HCO3)2 are also present in the groundwater. To avoid uncertainties involved in bicarbonate measurement and to consider that the electrical conductivity is not linearly related to the Cl concentration (De Louw et al 2011), we separated the entire data set into three classes.…”
Section: Relation Between Ec W and CLmentioning
confidence: 84%
“…Salt also accumulated in the shallow aquifer below Unterweser Marsch, Hadelner Marsch, and Elbmarsch due to Holocene transgressions (leading to saline water infiltrating vertically from the flooded area before the dykes were built). At Stade, a salt structure exists that contains a different geochemical signature than the saline water originating from the sea (Rahman et al 2018). The contribution of this salt structure to the groundwater salinity at Stade is yet to be quantified.…”
Section: Source Of Salinity In the Aquifermentioning
confidence: 99%
“…The geological and hydrogeological condition of this is complex and salinity distribution in vertical and horizontal direction is non-uniform. Groundwater quality is also heterogeneous (Rahman et al 2018). Therefore, a development of a density driven groundwater flow and transport model is a big challenge here.…”
Section: The Topsoil Projectmentioning
confidence: 99%
“…To develop the groundwater models, an integrated approach has been presented by Wiederhold et al (2017) and a modified version is shown in Figure 3. An interdisciplinary approach, considering geological, geophysical and geochemical information has been formulated for groundwater catchment characterization (see details in Rahman et al 2018). These information together with hydrological and meteorological information from several W E organizations (e.g., Germany's National Meteorological Service (DMD), Lower Saxony department of water, coastal and nature conservation (NLWKN) etc.)…”
Section: The Topsoil Projectmentioning
confidence: 99%
“…Einen zusammenfassenden Überblick dazu bieten Siemon et al (2020b). In diesem Beitrag steht die küstennahe Grundwasserversalzung Deus et al 2015;González et al 2021b;Rahman et al 2018) im Vordergrund.…”
Section: Introductionunclassified